Инженерная психология в системе подготовки специалистов по предупреждению и ликвидации чрезвычайных ситуаций - Kremen', Маркс; Gerasimchik, Александр; Bogdanovich, Алексей (Vestnik of the Institute for Command Engineers of the MES of the Republic of Belarus, 2013)
Major problems of engineering psychology are analyzed, their system is given. The authors pay special attention to specific ways of practical application of results of psychological research in the design of control systems in organization of information exchange of fire rescuer with various elements of technical systems.